ANALISIS POLA ASUH ORANG TUA TERHADAP MOTIVASI BELAJAR SIWA KELAS III SD NEGERI KEBON CAU IV KABUPATEN TANGERANG - Nur Latifah; Najib Hasan; Yulianti Dewi (STKIP Subang, 2023)
Children will become the next generation of families for the nation and state, and education will also be the development of children's lives in the future. Every child has various kinds of abilities and skills, so education is very important for every child, both formal and non-formal education can form a child's personality that is better, polite, intelligent, successful, responsible, and leads to a more advanced direction. Good parenting will produce a good relationship from both parties will bring it to a positive impact on the development of a child. Conversely, the poor quality of the relationship between parents and their children will cause conflict. Motivation and learning are two things that really influence. Learning is a relatively permanent change in behavior and potentially occurring as a result of practice and purpose-based reinforcement to achieve that goal. Parental awareness plays an important and responsible role in education, which is first and foremost in the family. Some of the factors causing the lack of student learning motivation are seen from the different backgrounds of the parents of students, both in terms of work, or busyness outside the home, economic conditions and so on which affect the lack of parental attention to their children.